Kepatuhan Diet Dengan Resiko Neuropati Perifer Pada Pasien Diabetus Melitus Di RS Prikasih Jakarta - Tesya Andri Wijayanti; Yeni Koto; Susaldi Susaldi (JOURNAL SAINS STUDENT RESEARCH, 2024)
A diet with energy and carbohydrate intake that does not meet your needs tends to result in uncontrolled blood sugar levels. Non-compliance with diet management by Diabetes Mellitus sufferers will cause uncontrolled blood sugar levels and complications such as kidney, heart, nearsighted eyes, gangrene and even having to undergo amputation of parts of the body that are badly injured. The aim of this research is the relationship between dietary compliance and the risk of peripheral neuropathy in diabetes mellitus patients at Prikasih Hospital, Jakarta. The research method that will be used is an analytical research design with a correlational design with a cross-sectional approach, a population of 50 respondents, a total sample technique and a sample size of 50 respondents. Using the non-parametric Rank Spearman Ro test. The results showed a relationship between diet compliance and the risk of peripheral neuropathy in Diabetes Mellitus patients at Prikasih Hospital, Jakarta with a P-Value of 0.016. Conclusion: Peripheral neuropathy with complaints including prickling sensations, numbness in the feet, decreased sensitivity to pain and temperature can occur in diabetes mellitus patients if diet is not maintained properly.